Profitability and voluntary disclosure of Brazilian equity companies - Rody, Paulo Henrique Amaral; Sousa, Anderson Fioresi; Souza , Thiago Roozevelt; Reina, Diane Rossi Maximiano (Contextus - Revista Contemporânea de Economia e Gestão, 2020)
This article verified whether profitability positively influences companies' voluntary disclosure level. To achieve the objective of this article, a Multiple Linear Regression (MLR) Analysis was used with fixed effect panel data, from all non-financial companies of B3 (Brazilian stock exchange), being 527 companies from the period from 2010 to 2018 (nine years), generating a total initial sample of 4,743 observations. Based on the results of the econometric model, we found that higher profitability is associated with lower voluntary disclosure levels of B3 listed companies. This evidence contradicts the hypothesis of the literature, that indicates a positive relationship between profitability and voluntary disclosure.